Analisis Peran Stakeholders dalam Pengembangan Pariwisata Siosar - Grace Ginting; Kismartini Kismartini; Tri Yuniningsih; Teuku Afrizal (Universitas Medan Area, 2021)
Siosar is one of the tourist areas located in Karo Regency, North Sumatra. The tourism development of Siosar tourism area involves the roles of stakeholders, namely government, private sector and community. The role of stakeholders is needed to carry out development including tourism development so that it can be carried out optimally. Stakeholders are individuals or groups involved in tourism development. The purpose of this research is to analyze the roles of stakeholders in developing the tourism area of Siosar. The research method used is a literature review study. The results showed that the role of stakeholders in the development of the Siosar tourism area was not significant. Siosar is a tourist area that has natural potential, agro-tourism, and others that must be developed properly. Each stakeholder plays its role, but has not given optimal results, there are still imbalances in roles and the obstacles faced indicate that stakeholders have not fully played their roles, both the roles of the government, the private sector and the community. The role of stakeholders is not yet optimal because there is no cooperation and communication that is well established. The local government should have collaborated with the private sector and the community to make efforts in developing tourism, so that tourism development in the Siosar tourism area can be more optimal and significant.